Depressive Symptoms Following Recent Sexual Assault: The Role of Drug and Alcohol Use, Acute Stress, and Assault Characteristics. Issue 11 (June 2021) - Dir, Allyson L.; Hahn, Christine; Jaffe, Anna E.; Stanton, Kimberley; Gilmore, Amanda K.
Sexual assault is a common traumatic experience that can have a wide-ranging impact on psychological functioning, including experience of depressive symptoms. Although many studies have examined lifetime rates of depression among those with sexual assault history, less is known regarding risk factors for depressive symptoms following recent sexual assault. The study examined whether drug use history is uniquely related to depressive symptoms following recent assault. N = 65 individuals, 95.4% female; 73.8% White; M ( SD )age = 28.89 (10.29), who had recently experienced sexual assault (less than 60 days) and completed a SAMFE (sexual assault medical forensic examination) were interviewed via phone and completed questionnaires regarding depressive and acute/post-traumatic stress symptoms and substance use history. Demographic information as well as information related to the assault was also collected. 68.7% of the sample reported clinically significant levels of depressive symptoms (PHQ-9, Patient Health Questionnaire, scores ⩾ 12). In a linear regression adjusted for acute/post-traumatic stress ( b = 0.26, p < .01) and other variables, polydrug use was significantly associated with depressive symptoms ( b = 3.26, p = .04). Single-drug use ( b = 0.96), physically forced sexual assault ( b = −1.11), victim–perpetrator relationship ( b = 0.15), prior sexual assault (b = −1.02), alcohol misuse ( b = −0.09), age ( b = 0.07), race ( b = 2.78), and days since assault ( b = −0.02) were not significantly associated with depressive symptoms (all p s > .05). Results highlight the potential role of drug use history in increasing risk of experiencing clinically significant depressive symptoms following recent assault.